Soil Water Characteristic Curve for a Granite Residual Soil: Experimental and Numerical Results - A. Topa Gomes (2011)
The seepage analysis in geotechnical problems, namely in excavations, was typically performed assuming saturated conditions in the ground. It is now know that the flow in the non saturated part of the ground assumes also relevant importance and hence it is vital to characterize its behaviour. The Soil Water Characteristic Curve (SWCC) of the soil is probably the most important parameter in defining this behaviour and particularly for estimating the permeability of the soil. This paper presents the definition of the SWCC for a granite residual soil using pressure plates and the filter paper method. Based on experimental data some equations are adjusted and the results obtained are discussed. At the end of the paper some predictions of the non saturated permeability of the ground are also performed.